North Korea's Mundane Revolution : Socialist Living and the Rise of Kim Il Sung, 1953-1965 - Schmid, Andre (Asia Pacific Modern ;, 2024)
When the crucial years after the Korean War are remembered today, histories about North Korea largely recount a grand epic of revolution centering on the ascent of Kim Il Sung to absolute power. Often overshadowed in this storyline, however, are the myriad ways the Korean population participated in party-state projects to rebuild their lives and country after the devastation of the war. North Korea's Mundane Revolution traces the origins of the country's long-term durability in the questions that Korean women and men raised about the modern individual, housing, family life, and consumption. Using a wide range of overlooked sources, Andre Schmid examines the formation of a gendered socialist lifestyle in North Korea by focusing on the localized processes of socioeconomic and cultural change. This style of ";New Living"; replaced radical definitions of gender and class revolution with the politics of individual self-reform and cultural elevation, leading to a depoliticization of the country's political culture in the very years that Kim Il Sung rose to power.